IR-SPECTROSCOPIC AND THERMOGRAVIMETRIC STUDIES OF THE COBALT, COPPER, AND ZINC COMPLEXES BASED ON GLYPHOSATE: DOI: https://doi.org/10.17721/1728-2209.2018.1(55).7 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
The complexes with Co(II), Cu(II), and Zn(II) based on glyphosate (N-phosphonomethylglycine) have been synthesized and studied by means of IR-, electron diffusion spectroscopies, thermogravimetric, and elemental analysis. The coordination behavior between glyphosate and carbacylamidophosphates was compared. By means of IR spectroscopy, it was found that regardless of the ratio of reacting components (metal salt and glyphosate) the coordination compounds of the same type for each metal are always formed. The spectrum of the glyphosate and complexes with it can be divided into two parts, corresponding to the different donor groups of the ligand. Between 1500 and 1800 cm-1 strong peaks are found, mostly associated with stretching motions of the carboxylate group, while the region 800–1200 cm-1 is dominated by peaks originating from the phosphonate. The changes in frequencies of phosphate P–O  (Δ(PО)=127 cm-1 for Na4CuL2, 144 cm-1 for Na4CоL2 and 21 cm-1 for ZnHL);  NH– and C=O (Δ(CО)=102 cm-1 for Na4CuL2, 133cm-1 for Na4CоL2, and 123 cm1- for ZnHL) peaks indicate the involvement of these groups in coordination. The v(C–O)a is shifted to higher frequency and broadened. The thermal decomposition process of glyphosate was studied by the DT and TG analysis. The results showed that the thermal decomposition temperature of glyphosate was above 198°C. The decomposition process was divided into three stages: the zero stage is the decomposition of impurities, and the mass loss in the first and second stage may be methylene and carbonyl, respectively. It has been found that the ligand in the mentioned complexes is coordinated tridentivly via the nitrogen atom of amino group and oxygen atoms of the carbonyl and phosphate groups. The electronic spectrum of diffuse reflection of the cobalt (II) complex showed only one peak  in the 534 nm region, corresponding to 4T1g (F)→ 4T1g (P) transition. This fact indicating the octahedral environment of the cobalt atom in complexes and causes its pink coloration. On the base of TGA and DTA analysis, IR spectroscopy and elemental analysis, the following compositions of the complexes were proposed: Na4CuL2, Na4CоL2 and ZnHL. Based on the literature data and our studies it was assumed that above structures contain five membered chelate rings with the amine, carboxylate, and phosphonate groups of the glyphosate ligand involved in chelation. Unlike 3d-metal complexes with carbacylamidophosphates, the phosphoryl group of glyphosate does not participate in coordination.
Keywords: carbacylamidophosphates; glyphosate; complexes 3-d metals; thermogravimetric analysis